Women"s statement at the 1990 Rustenburg Church Conference: Still an important voice from the past - Merwe, Johan M. van der (HTS teologiese studies, 2022)
The Rustenburg Conference of churches that took place in 1990 was a critical turning point for Christianity in South Africa. Besides the important declaration at the end of the conference, a statement was also made by the women at the conference. Although this statement is lesser known, it was and still is of utmost importance because it addresses the plight of women in South Africa. The focus of this article is the relevance of the statement made by the women more than 30 years later. The article is written from a church historical perspective. To achieve this objective, the research in this article is based on qualitative literature search. It focuses on relevant literature that includes books, scholarly articles, online articles and scientific data provided by Statistics South Africa. It starts with a brief overview of the conference and important events that took place; it then moves on to the statement by the women at the conference before arguing that the content of the statement still is an important voice from the past that reminds us of the plight of women in South Africa. The role of the church as an important agent of change is then discussed briefly before concluding with an example of a programme by the South African Council of Churches (SACC) that is aimed at change in society.Contribution: In the conclusion, the author proposes a South African conference for women where current programmes can be synchronised and planning for the future can be done.